COVID-19 and the state - Rachel M. Gisselquist; Andrea Vaccaro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We expect effective state institutions to matter in a country's ability to respond to crises. Yet notably in the first year of the COVID-19 pandemic, what has stood out in simple global snapshots is that wealthier countries with stronger institutions have had the highest numbers of cases and fatalities on average, while many poorer countries with weaker institutions have been praised for more effective pandemic responses. What explains this seeming puzzle? We re-consider these relationships in the cross-country data, drawing on measures of the state, COVID's health impact, and pandemic policy response. In brief, our analysis suggests that, when appropriate additional factors are taken into account, the expected relationship between state effectiveness and pandemic health outcomes does in fact pertain. Our findings also offer insight into how different dimensions of the state influence policy and outcomes, as well as how countries compare in terms of institutional effectiveness.
Keywords: I15; I18; H12; O57; 330; COVID-19; pandemic; state; state capacity; state effectiveness; state legitimacy; state authority